Efficient, Repeated Adenovirus-Mediated Gene Transfer in Mice Lacking both Tumor Necrosis Factor Alpha and Lymphotoxin α - Benihoud, Karim (American Society for Microbiology, 1998)
The efficiency of adenovirus-mediated gene transfer is now well established. However, the cellular and the humoral immune responses triggered by vector injection lead to the rapid elimination of the transduced cells and preclude any efficient readministration. The present investigation focuses on the role of tumor necrosis factor alpha (TNF-α), a proinflammatory cytokine, and the related cytokine lymphotoxin α (LTα), in mounting an immune reaction against recombinant adenovirus vectors. After gene transfer in the liver, mice genetically deficient for both cytokines (TNF-α/LTα(−/−)), in comparison with normal mice, presented a weak acute-phase inflammatory reaction, a reduction in cellular infiltrates in the liver, and a severely impaired T-cell proliferative response to both Adenoviral and transgene product antigens. Moreover, we observed a strong reduction in the humoral response to the vector and the transgene product, with a drastic reduction of anti-adenovirus immunoglobulin A and G antibody isotypes. In addition, the reduction in antibody response observed in TNF-α/LTα(−/−) and TNF-α/LTα(+/−) mice versus TNF-α/LTα(+/+) mice links antibody levels to TNF-α/LTα gene dosage. Due to the absence of neutralizing antibodies, the TNF-α/LTα knockout mice successfully express a second gene transduced by a second vector injection. The discovery of the pivotal role played by TNF-α in controlling the antibody response against adenovirus will allow more efficient adenovirus-based strategies for gene therapy to be proposed.